Reversal of Experimental Liver Damage after Transplantation of Stem-Derived Cells Detected by FTIR Spectroscopy - Danna Ye; Philip Heraud; Rangsun Parnpai; Tong Li (Hindawi Limited, 2017)
The transplantation of autologous BM-MSCs holds great potential for treating end-stage liver diseases. The aim of this study was to compare the efficiency of transplanted rBM-MSCs and rBM-MSC-derived differentiated stem cells (rBM-MSC-DSCs) for suppression of dimethylnitrosamine-injured liver damage in rat model. Synchrotron radiation Fourier-transform infrared (SR-FTIR) microspectroscopy was applied to investigate changes in the macromolecular composition. Transplantation of rBM-MSC-DSCs into liver-injured rats restored their serum albumin level and significantly suppressed transaminase activity as well as the morphological manifestations of liver disease. The regenerative effects of rBM-MSC-DSCs were corroborated unequivocally by the phenotypic difference analysis between liver tissues revealed by infrared spectroscopy. Spectroscopic changes in the spectral region from 1190-970 cm−1 (bands with absorbance maxima at 1150 cm−1, 1081 cm−1, and 1026 cm−1) indicated decreased levels of carbohydrates, in rBM-MSC-DSC-transplanted livers, compared with untreated and rBM-MSC--transplanted animals. Principal component analysis (PCA) of spectra acquired from liver tissue could readily discriminate rBM-MSC-DSC-transplanted animals from the untreated and rBM-MSC-transplanted animals. We conclude that the transplantation of rBM-MSC-DSCs effectively treats liver disease in rats and SR-FTIR microspectroscopy provides important insights into the fundamental biochemical alterations induced by the stem-derived cell transplantation, including an objective "signature" of the regenerative effects of stem cell therapy upon liver injury.